The contribution of analytical accounting to enhancing performance in Algerian government agencies An analysis of Ahmed Medaghari Hospital in Saida City - Mahmoudi , Kadda; Zeggai, Diab; Kadda, Aissa (Journal of Research in Finance and Accounting, 2025)
This study aims to highlight the impact of the use of analytical accounting in improving performance within public institutions, through the case study of Ahmed Medaghari Hospital – Saida City. The study relied on a questionnaire distributed to a sample of 60 employees, and the data was analyzed using different statistical tools. The results showed that the awareness of the importance of analytical accounting was average, while the actual degree of application is relatively weak, and it was found that organizational and human obstacles represent a real obstacle to application. Regression analysis confirmed that analytical accounting contributes to poor performance improvement (R² =0.024). The study recommended the need to modernize accounting information systems, train human cadres, and provide administrative support.